An Alternative to Developmental Coursework: Critical Skill Integration - Robin A. Lukes (Academic Chairpersons Conference Proceedings, 2017)
This interactive session explores ways in which an associate degree liberal arts and sciences department eliminated developmental coursework through the integration of critical skills (reading, reasoning, thinking and math) into the core curriculum. We will discuss the importance of honoring disciplinary perspectives while also considering how best to deliver a core for associate degree adult learners.
Keywords: Critical Skill Integration; Core Curriculum; Developmental Education